Pan-Mitogenomics Approach Discovers Diversity and Dynamism in the Prominent Brown Rot Fungal Pathogens - Yildiz, Gozde; Ozkilinc, Hilal (Frontiers in Microbiology, 2021)
Monilinia fructicola and M. laxa species are the most destructive and economically devastating fungal plant pathogens causing brown-rot disease on stone and pome fruits worldwide. Mitochondrial genomes (mitogenomes) play critical roles influencing the mechanisms and directions of the evolution of fungal pathogens. The pan-mitogenomics approach predicts core and accessory regions of the mitochondrial genomes and explains the gain or loss of variation within and between species. The present study is a fungal pan-mitogenome of M. fructicola (N=8) and M. laxa (N=8) species. The completely sequenced and annotated mitogenomes showed high variability in size within and between the species. The mitogenomes of M. laxa were larger, rangingfrom 178,351 bp to 179,780 bp, than the mitogenomes of M. fructicola, ranging from 158,607 bp to 167,868 bp. However, size variation within the species showed that M. fructicola isolates were more variable in the size range than M. laxa isolates. All the mitogenomes included conserved mitochondrial genes, as well as variable regions including different mobile introns encoding homing endonucleases or maturase, non-coding introns, and repetitive elements. The linear model analysis supported the hypothesis that the mitogenome size expansion is due to presence of variable (accessory) regions. Gene synteny was mostly conserved among all samples, with the exception for order of the rps3 where one isolate showed. The mitogenomes presented AT richness, however, A/T and G/C skew varied among the mitochondrial genes. The purifying selection was detected in almost all the protein-coding genes between the species. However, cytochrome b was the only gene showing a positive selection signal among the total samples. Combined datasets of amino acid sequences of 14 core mitochondrial protein coding genes and rps3 obtained from this study together with published mitochondrial genome sequences from some other species from Heliotales were used to infer a Maximum Likelihood (ML) phylogenetic tree. ML tree indicated that both Monilinia species highly diverged from each other as well some other fungal species from the same order. Mitogenomes harbor much information about the evolution of fungal plant pathogens, which could be useful to predict pathogenic life strategies.